Prenylated acylphloroglucinol alcohols and peroxides from Hypericum coris - Carlos Henrique Corrêa dos Santos; Pauline Stark; Paride Rizzo; Katrin Franke; Ludger Wessjohann (Phytochemistry Letters, 2023)

Correction to: Simple and robust multiple shoot regeneration and root induction cycle from different explants of Hypericum perforatum L. genotypes - Beena M. Ravindran; Paride Rizzo; Katrin Franke; Jörg Fuchs; John D’Auria (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Correction to: Simple and robust multiple shoot regeneration and root induction cycle from different explants of Hypericum perforatum L. genotypes - Beena M. Ravindran; Paride Rizzo; Katrin Franke; Jörg Fuchs; John D’Auria (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Simple and robust multiple shoot regeneration and root induction cycle from different explants of Hypericum perforatum L. genotypes - Beena M. Ravindran; Paride Rizzo; Katrin Franke; Jörg Fuchs; John D’Auria (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)
Hypericum perforatum L. commonly known as Saint John’s Wort (SJW) is an economically important medicinal plant known for accumulating its valuable bioactive compounds in a compartmentalized fashion. The dark glands are very rich in hypericin, and translucent glands are filled with hyperforin. The antibiotic properties of the afore mentioned bioactive compounds make it hard to establish tissue regeneration protocols essential to put in place a transformation platform that is required for testing gene function in this challenging species. In this study, we report the establishment of a regeneration and root induction cycle from different types of explants. The regeneration cycle was set up for the continuous supply of roots and leaf explants for downstream transformation experiments. The most effective medium to obtain multiple shoot-buds from node cultures was MS (Murashige and Skoog, Physiol Plant 15:473–497, 1962) medium supplemented with 0.5 mg L −1 6-Benzylaminopurine (BAP) and 0.5 mg L −1 indole-3-butyric acid (IBA). The same combination yielded copious amounts of shoots from root and leaf explants as well. For rooting the elongated shoots, MS medium devoid of plant growth regulators (PGRs) was sufficient. Nevertheless, addition of a low amount of IBA improved the quantity and quality of roots induced. Additionally, the roots obtained on a medium containing IBA readily developed shoot buds.